The mediating role of feelings of hopelessness and repetitive negative thinking in the relationship between perfectionism and depressive symptoms among medical students with suicidal ideation - Ali Hosseinzadeh Oskouei; Reyhaneh Sardarzehi; Mohammad Sadegh Zamani Zarchi; Seyed Alireza Tavallaei Zavareh; Jamal Shams; Amir Sam Kianimoghadam; Abbas Masjedi Arani (Frontiers in Psychiatry)
BackgroundPerfectionism and depressive symptoms are among psychological concerns in medical students with suicidal ideation. While studies suggest a link between perfectionism and depression, the role of mediating mechanisms remains unclear.ObjectiveThis study aimed to examine the mediating role of hopelessness and repetitive negative thinking in the relationship between perfectionism and depressive symptoms among Iranian medical students.MethodsThe research employed a descriptive-correlational design using structural equation modeling (SEM). The study population comprised all medical students in Tehran in 2024, from which 355 individuals were selected through purposive sampling. Data were collected using the Beck Scale for Suicidal Ideation (BSSI), Tehran Multidimensional Perfectionism Scale (TMPS), Beck Depression Inventory (BDI-II), Repetitive Negative Thinking Questionnaire (RNTQ), and the Beck Hopelessness Scale (BHS). The data were analyzed using structural equation modeling.ResultsThe results indicated that the proposed model demonstrated an excellent fit, and perfectionism was significantly and directly associated with depressive symptoms (p < 0.01). Additionally, perfectionism indirectly predicted depressive symptoms (p < 0.001) through hopelessness (β = 0.35) and repetitive negative thinking (β = 0.37). Together, perfectionism, hopelessness, and repetitive negative thinking accounted for 58% of the variance in depressive symptoms (R² = 0.58).ConclusionsThese findings suggest that perfectionism contributes to an increase in depressive symptoms both directly and indirectly, by intensifying feelings of hopelessness and repetitive negative thinking.